(untitled) (Research, Society and Development, 2023)
This descriptive epidemiological study aimed to explore the characteristics and impact of hospitalizations in patients with bronchitis, chronic respiratory diseases and emphysema. Data collection was performed using the TABNET system, provided by DATASUS, covering the period from January 2013 to January 2023. The information was organized by age group, gender, region and period of hospitalization. Statistical analyzes were performed using SPSS version 22.0. The results showed a gradual increase in hospitalizations for chronic obstructive pulmonary diseases with advancing age in different regions of Brazil. These data can help in the development of more targeted strategies for the prevention, diagnosis and treatment of these conditions. Considering the variations in distribution by gender and region, it is important to understand the specific risk factors and epidemiological characteristics that contribute to these differences. It was concluded that the prevalence of hospitalizations for emphysema, bronchitis and chronic respiratory diseases is statistically higher in the Southeast region, in men and in the age group from 60 years old. Several factors may be related to these findings, such as population density, access to health services, the population’s lifestyle, pollution rates and climate change. It is important to consider regional differences, including climate and socioeconomic conditions, to understand these disparities. This analysis can contribute to the development of more specific public policies in each region, which can reduce public health costs.